534 Results of the "decade of road safety action" in Colombia. 2010–2015. (1st September 2016) - Cabrera, Gustavo; Rodríguez, Jorge; Camelo, Fredy
Abstract : Background: In the 1990's, the United Nations set the standards for confronting the increasing issue of traffic injuries and fatalities (TIF). In Colombia, the 2013–2021 National Road Safety Plan was created to implement guidelines and facilitate inter-sector coordination of the strategic pillars proposed in the program Decade of Road Safety Action-DRSA. This study shows the results of the first five years of the DRSA program in Colombia. Methods: This descriptive, longitudinal study analyses the behaviour of TIF in Colombia from 2010 to 2015. The injury and fatality records were obtained from the Colombian National Institute of Legal Medicine and from the Colombian National Statistics Department. The number of vehicles was obtained from the Unified National Transit Registry. Adjusted fatality rates were estimated. A lineal regression model was made to correlate the fatality rates with the overall increase in the number of vehicles adjusted by population during the study period. Results: The information sources differ as far as percentages were concerned (1.3%–6.5%), but they coincided in the fact that fatalities increased by around 40% (2014). 37% of the fatalities occurred in three provincial departments: Antioquia (14.4%), Valle (12.5%) and Bogotá (10.1%). The average fatality rate for 2014 was nearly 14.0/100, 000 inhabitants; although it was higher in the provincial departments of Casanare (37.7), Arauca (27.9), Meta (26.6), and Cesar (25.7). There was a positive correlation between TIFs and the increase in the number of vehicles in Colombia (p < 0.001). Conclusions: Road safety management in Colombia is restricted due to the lack of a leading agency to direct, control, and manage policies. Although a decree to create a National Road Safety Agency was issued in 2013, the year 2015 is now closing and such agency has not initiated operations. Poor implementation and non-compliance with traffic laws and regulations seem to be the main cause for traffic accidents.